Especificação de perfis e regras, baseada em ontologias, para adaptação de conteúdo na internet - Forte, Marcos (2006)
The last decade was scenery of big transformations, among them the social revolution caused by Internet stand out, changing the way that people find information, communicate and buy products and services. Moreover, the convergence of telephony, informatics and consume electronic, supplies more and more mobile devices equipped with Internet access through wireless network. This changing caused a big problem to the Internet content available at Web: how the same content should be adjusted to different kinds of users witch have particular preferences, and be presented in mobile devices featured with a big diversity of functionalities? To solve this problem, many research proposals are been developed at content adaptation area. One challenge of this area is define, from a user request, witch adaptation services are necessary and these execute sequence. In order to have the best decision, delivery context and the available services have to be acknowledged. This information are described at profiles and rules, considering that nowadays the majority of proposed solutions are based in proprietary models and not compatibles among each other. As well, the discovery of services generally is strongly based on syntactic matching, what weak the discovery and composition of services. Intending to contribute with content adaptation area, this dissertation defines an ontology-based set of profiles and reused. Furthermore, shows how the rules have to be integrated with services profiles, providing a rules and profiles independent solution. Also are presented the benefits use of semantics at match and composition of services in an open environment such as the Web. The implementation and the case study of this proposition were based at a component-based content adaptation framework. With the purpose of extend its functionality, in order to support ontology, and others necessary functions, components were reused, adapted or created. This extensions made possible achieve the case study and the validation of proposed solution.